Faith, Culture, and Hospitality: Redefining Tourism Experience in the Hajj Sector - Mostafa Omran (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
As one of the most holy travels in Islam, the Hajj pilgrimage has come to be more than just a religious duty to become a multifaceted combination of religion, culture, hospitality, technology, and policy. By billions of Muslims crossing borders to complete this spiritual duty, their expectations are becoming merged more and more towards a mixture of cultural identity, digital cover, and halal-compliant service. In this article, the author attempts to provide answers to the question under how the Hajj industry is being redefined in terms of Islamic values, hospitality and standards, technology and the socio-political pressures of a global world. It relies on extensive academic discussion to explore the commodification of spiritual experience, how Hajj industry survives after COVID-19, how AI and digital technology can improve pilgrim experience, and the need to develop culturally intelligent and ethically sound tourism paradigms. This work has fully integrated 31 academic sources in different areas which have helped in understanding the changing environment of Hajj better and to implement a structure of spiritual enriching pilgrimage tourism in the 21 st century.
Keywords: Hajj tourism; Islamic hospitality; Halal travel; spiritual experience; religious tourism; digital pilgrimage; Muslim travelers; faith-based tourism; cultural identity; COVID-19 tourism recovery